Corpore et animo praepurgata. La Teología mariana de la Inmaculada Concepción en un sermón inédito del siglo XVIII (2021)
Several sermons preached by the Dominican friars of New Granada during the 18th century can be found in the Historical Archives of the Province San Luis Bertrán of Colombia (AHPSBC). Based on the historical-critical and theological method, a mariological analysis of the sermon De Concepción: Beatus venter qui te portavit (Lc 11, 27), preached in 1797, is made by identifying theological categories based on biblical and patristic sources, as well as the other ecclesiastical writers proposed by the author. Since these texts have been endowed with an iconic and apologetic language, contributions to the History of Mariology are provided through the paleographic, archival, diplomatic and codicological analysis of the sermon selected.